Development and Characterization of Sustainable Bioplastic Films Using Cellulose Extracted from Prosopis juliflora - Marichelvam M K; Manimaran P; Anish Khan; Geetha M; Kandakodeeswaran K; Ahmed H. Abduljabbar; Edi Syafri; Mohammad A. Wazzan; Huda Wazzan; Waseem Khan (Journal of Natural Fibers, 2023)
To diminish the environmental impacts instigated by plastics, investigators recommended bioplastics. In the current work, an attempt is made to develop sustainable bioplastics from waste plants. Cellulose was extracted from the wood of Prosopis juliflora. The Prosopis juliflora wood was cut and ground into powder. The powder was washed with water and subjected to several chemical treatments to extract the cellulose. The bioplastic film samples were produced using it. Six different samples were prepared by varying the composition of cellulose, gelatin, citric acid, and glycerol. Several tests were carried out on samples developed as per ASTM standards, and the results were compared with the existing bioplastics. The test results indicated that sample 1 has a maximum tensile strength of 7.73 MPa. The average bursting strength of the bioplastic film is 12.44 kg/cm2, which is better than the other bioplastics reported in the literature. The average biodegradability of developed bioplastic films is approximately 59.43%. The results revealed that the Prosopis juliflora cellulose-based bioplastics would be a better substitute for conventional plastics.